The effect of quenching cooling rate on the microstructure and tensile/compressive behaviors of 2Cr12Ni martensitic stainless steel - Rui Luo; Jiayu Chen; Hengnan Ding; Pengcheng Zhang; Jun Liao; Yang Yu; Huixia Xu; Xiaochen Xu; Tianming Liu; Xiaonong Cheng (Journal of Materials Research and Technology)
Martensitic stainless steel is renowned for its exceptional hardness and corrosion resistance, making it a preferred material for large plastic molds. A notable disparity exists between the cooling rates at the surface and core of these molds during the quenching process, which leads to variations in the quenching microstructures and mechanical properties and, consequently, the material's service performance. Understanding the relationship between quenching cooling rates and the resulting microstructures is critical. In this study, a Gleeble-3500 thermal simulation tester was employed to investigate the mechanical properties and microstructure evolution in 2Cr12Ni martensitic stainless steel at cooling rates ranging from 0.05 to 20 °C/s. The results indicate that with the increase of the quenching cooling rate, the Vickers hardness of 2Cr12Ni remains relatively stable, ranging from 602.1 to 611.0 HV10; the tensile strength and elongation gradually increase from 898.07 MPa to 1.5 % at 0.05 °C/s to 1733.63 MPa and 23.5 % at 20 °C/s; the compressive strength remains basically the same, and gradually decreases with the increasing compression temperature. The quenching cooling rate significantly influences the quantity and size of precipitates and residual austenite content in 2Cr12Ni steel after quenching. Specifically, the number and size of M23C6 precipitates gradually decrease while the material's grain size remains consistent at approximately 3.4 μm. The volume fraction of residual austenite increases with the cooling rate, transitioning from a fine strip-like morphology to a thin plate-like morphology. Furthermore, the mechanisms of the microstructure and mechanical properties evolutions were also briefly discussed.